Sport-related anxiety: current insights - Ford JL; Ildefonso K; Jones ML; Arvinen-Barrow M (Dove Medical Press, 2017)
Jessica L Ford, Kenneth Ildefonso, Megan L Jones, Monna Arvinen-Barrow Department of Kinesiology, Integrative Health Care & Performance Unit, University of Wisconsin-Milwaukee, Milwaukee, WI, USA Abstract: To date, much research has been devoted to understanding how anxiety can affect sport performance, both in practice and in competitive settings. It is well known that sport has the potential for high levels of stress and anxiety, and that practicing and employing a range of psychological strategies can be beneficial in anxiety management. Equally, growing evidence also suggests that anxiety can play a role in sport injury prevention, occurrence, rehabilitation, and the return to sport process. The purpose of this paper is to provide current insights into sport-related anxiety. More specifically, it will provide the reader with definitions and theoretical conceptualizations of sport-related anxiety. This will be followed by making a case for considering the term "performance" to be broader than activities associated with sport-related performance in practice and competition, by including performance activities associated with sport injury prevention, rehabilitation, and the return to sport process. The paper will then highlight the importance of recognizing early signs and symptoms of anxiety, and the potential need for referral. Finally, the conclusions will emphasize the need for appropriate, client-specific, and practitioner competent care for athletes experiencing sport-related anxiety. Keywords: anxiety, sport, performance, injury, sport medicine professional, sport psychology, mental health